Pemanfaatan Limbah Rambut Manusia sebagai Media Tanam Hidroponik Substrat pada Kailan - Niken Pusparini; Dwi Harjoko; Retna Bandriyati Arniputri (Agrosains : Jurnal Penelitian Agronomi, 2019)
This study aims to examine the use of human hair waste as a substrate hydroponic media in enhancing scientific innovation and agricultural development. This research was conducted in a greenhouse, Faculty of Agriculture, Sebelas Maret University, Surakarta, from July 2018 to October 2018. This experimental using a completely randomized design (CRD) method with one treatment factor and 14 levels repeated 4 times. The treatment includes washing hair waste (water, NaOH and detergent) and a combination of hair waste: husk charcoal (1: 3; 1: 2 and 3: 1). In this study, the control treatment used sand media. Observation variables observed were leaf area index, number of leaves, plant height, stem diameter, root length, root weight, root volume, fresh weight and dry weight of plants. Data acquisition was analyzed by analysis of variance and if there were significant differences, further testing was carried out with Duncan Multiple Range Test (DMRT) at the level of 5%. The results showed that human hair waste was less optimal as an alternative medium for hydroponic substrate systems. Treatment of hair waste: combination of 1: 3 husk charcoal in all washings gives the highest average yield on all observation variables. In all washing treatments (Water, NaOH and detergent) the highest average yield was dominated by washing using detergent ie leaf area index (55.35 cm2), root volume (1.19 ml), fresh weight (22.03 g) and dry weight (2.83 g).